1999
DOI: 10.1093/toxsci/51.1.80
|View full text |Cite
|
Sign up to set email alerts
|

Chemically induced oxidative stress disrupts the E-cadherin/catenin cell adhesion complex

Abstract: The impact of xenobiotics on intercellular adhesion, a fundamental biological process regulating most, if not all, cellular pathways, has been sparsely investigated. Cell-cell adhesion is regulated in the epithelium primarily by the E-cadherin/catenin complex. To characterize the impact of oxidative stress on the E-cadherin/catenin complex, precision-cut mouse liver slices were challenged with two model compounds for the generation of oxidative stress, diamide (DA; 25-250 microM) or t-butylhydroperoxide (tBHP;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
28
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 38 publications
4
28
0
1
Order By: Relevance
“…These findings raise the possibility that overproduction of OFR resulting from mitochondrial dysfunction, due to lack of supply of VFAs, may damage TJs by reducing the tissue content of claudin-3 and occludin. This hypothesis is supported by other studies of our group that have analyzed the protein components of AJs (E-cadherin and β-catenin) in an experimental model of CDC and showed that the levels of both proteins decreased with the time of fecal diversion and was correlated with overproduction of OFR by cells of colonic mucosa devoid from fecal stream [8][9][10] . This evidence reinforces the importance of VFAs in the maintenance the integrity of both TJs and AJs in experimental CDC.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…These findings raise the possibility that overproduction of OFR resulting from mitochondrial dysfunction, due to lack of supply of VFAs, may damage TJs by reducing the tissue content of claudin-3 and occludin. This hypothesis is supported by other studies of our group that have analyzed the protein components of AJs (E-cadherin and β-catenin) in an experimental model of CDC and showed that the levels of both proteins decreased with the time of fecal diversion and was correlated with overproduction of OFR by cells of colonic mucosa devoid from fecal stream [8][9][10] . This evidence reinforces the importance of VFAs in the maintenance the integrity of both TJs and AJs in experimental CDC.…”
supporting
confidence: 82%
“…In oxidative stress, the increase in the production of OFR, mainly hydroxyl radical (OH) can react with constitute substances of the colonic epithelial mucosa causing breakdown of the different structural defense mechanisms of the colonic barrier allowing the bacterial infiltration of the internal environment 4,7 . Studies showed that over production of OFR reduce and modify the mucus layer that covers the colonic mucosa, causes lipid peroxidation of the cell membranes, break the proteins constituents of adherents junctions (AJs) and tight junctions (TJs) [8][9][10][11] . Experimentally it has been demonstrated that the rupture of the epithelial barrier are related to higher levels of OFR and the development of CDC 9,10 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of Ecadherin might also be associated with the resistance of cancer cells to chemotherapy because it promotes cancer progression and metastasis (Arumugam et al, 2009;Huber et al, 2005;Wheelock et al, 2008). Oxidative stress disrupts the E-cadherin and catenin cell-adhesion complex (Parrish et al, 1999;Rao et al, 2002). Thus, it is plausible that E-cadherin might affect Nrf2 activity in response to oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of the adherens catenin-cadherin complex is integral in disruption of PTC adhesion in the early stages of tubulointerstitial fibrosis [17,22,23]. The most extensively studied cadherin is E-cadherin which typically resides in epithelial tissue; however, recent data suggest that N-cadherin is specific to the rat PTCs and binds cytoskeletal components that provide a structural foundation for adherens junctions [22,24]. Cadherins not only function as static structural components of adherens junctions, but also play an important role in metabolic signaling pathways [25,26].…”
Section: Introductionmentioning
confidence: 99%